Estratégias de criação de valor: um estudo sobre o crescimento via Marketplace de produtos do ramo industrial - Beletati, Bruno Henrique da Silva (2024)
This research sought to understand how a company in the industrial sector adopted the Marketplace as a strategic tool for creating and capturing value. The methodological approach of this exploratory, qualitative research was based on the Case Study method. Data collection was carried out through a semi-structured interview script, carried out with professionals responsible for the management and operation of the Marketplace, as well as in document analysis and information from the company's website. The case study revealed that the marketplace made it possible to exceed revenue goals, omnichannel integration, and innovation through greater data collection and reduced operational costs. However, challenges such as high paid traffic costs, resistance from trading partners, and logistical complexities were identified and overcome through well-planned strategies. The survey concludes that the marketplace was essential to modernize operations, create new market opportunities and strengthen Belgo Bekaert's competitiveness, standing out as an example of digital innovation in the industrial sector